The Effect of CaO Catalyst Mass from Golden Snail Shell (Pomacea Canaliculata Lamarck) on Transesterification Reaction - Rahman, Fachtur; Rodiah, Siti (ALKIMIA, 2020)
Biodiesel derived from waste encourages the development of environment-friendly alternative energy. One of the wastes that can be used as biodiesel is waste cooking oil. Biodiesel from waste cooking oil has some advantages such as non-toxic, less Carbon monoxide (CO), and environment-friendly. The produce of biodiesel from waste cooking oil was through transesterification reaction using CaO catalyst derived from golden snail shell. This study aimed to determine the optimum amount of catalyst that produced the highest yield. In this study, methanol was used as solvent by the molar ratio of methanol/waste cooking oil of 30:1, reaction temperature of 65˚C, reaction time for 2 hour, and variations of amount catalyst 3%, 5% and 7% by weight waste cooking oil. Biodiesel was analyzed by Gas Chromatography-Mass Spectroscopy showed that the highest yield achieved using 7% catalyst amounts was 93.28%.